Effect of steaming and roasting on the quality and resistant starch of brown rice flour with high amylose content. (15th September 2022) - Park, Jiyoung; Oh, Sea-Kwan; Chung, Hyun-Jung; Shin, Dong Sun; Choi, Induck; Park, Hyun-Jin
Abstract: The high-amylose rice cultivar Dodamssal (DDS), a potentially nutritious functional food, contains resistant starch (RS). However, its RS content varies with the processing method used. In this study, heat treatment was used to produce rice powder with enhanced RS content. The rice powder quality was improved by steaming rough rice and brown rice for 30 min and roasting the brown rice at 240 °C for 10 min. Brown rice flour (BRF) made from steamed rough rice and roasted DDS (SRRD) had higher RS content (14%), ratio of fine particle sizes (0–20 μm), and gelatinization degree (GD), as well as lower mean particle size (51 μm) and in vitro glycemic index than did roasted DDS. Contrastingly, BRF prepared from steamed brown rice and roasted DDS with high GD had low RS content (12%) and high mean particle size (56 μm). Hence, SRRD-BRF improves powder quality and may be beneficial for nutritious functional food production. Highlights: Steaming rough rice and roasting Dodamssal improves brown rice flour (BRF) quality. Treated BRF has higher resistant starch content. Ratio of fine particle size and gelatinization degree is higher in treated BRF. Treated BRF has lower mean particle size, in vitro glycemic index. Steaming and roasting rough rice may improve the quality of nutritious foods.